An Efficient and Earth‐Abundant Oxygen‐Evolving Electrocatalyst Based on Amorphous Metal Borides. Issue 1 (4th September 2017) - Nsanzimana, Jean Marie Vianney; Peng, Yuecheng; Xu, Yang Yang; Thia, Larissa; Wang, Cheng; Xia, Bao Yu; Wang, Xin
Abstract: Cost‐effective and efficient oxygen‐evolving electrocatalysts are urgently required for energy storage and conversion technologies. In this work, an amorphous trimetallic boride nanocatalyst (Fe–Co–2.3Ni–B) prepared by a simple approach is reported as a highly efficient oxygen evolution reaction electrocatalyst. It exhibits an overpotential (η) of 274 mV to deliver a geometric current density ( j geo ) of 10 mA cm −2, a small Tafel slope of 38 mV dec −1, and excellent long‐term durability at a mass loading of 0.3 mg cm −2 . The impressive electrocatalytic performance originates from the unique amorphous multimetal–metalloid complex nanostructure. From application's point of view, this work holds great promise as this process is simple and allows for large‐scale production of cheap, yet efficient, material. Abstract : Amorphous trimetallic boride demonstrates impressive electrocatalytic oxygen evolution activity, which originates from the tuned electronic properties of the constituent elements. Such an earth‐abundant boride electrocatalyst holds great promise for practical applications in water electrosplitting devices as the synthesis process is simple and allows for large‐scale production of cheap, yet efficient, material.